The collected letters of William Morris. - Morris, William, 1834-1896 (Princeton University Press, 1987)
The years covered in this volume, 1881 through 1888, are among the most vigorous in Morris's career. They record the sharp swing from optimism that public events can be affected by political ideas to disillusion about the people holding the ideas, and finally show the signs--in 1888--of a new, more personal, beginning and the reformulated purpose to come. Moreover, the letters, as always tell us who among Morris's friends and associates were most important to him in the years in which they were written. They also address several matters essential for an understandingof Morris: his definition of the word "political"; his shift from writing poetry to prose; and his complex of interests embracing language, narrative, and the decorative arts
Keywords: Morris, William, -- 1834-1896. -- Correspondence.; Correspondence (Morris, William); Authors, English -- 19th century -- Correspondence.; Socialists -- Great Britain -- Correspondence.; Designers -- Great Britain -- Correspondence.; Écrivains anglais -- 19e siècle -- Correspondance.; Designers -- Grande-Bretagne -- Correspondance.; BIOGRAPHY & AUTOBIOGRAPHY -- General.; BIOGRAPHY & AUTOBIOGRAPHY -- Literary.; POETRY -- English, Irish, Scottish, Welsh.; Authors, English; Designers; Socialists; Great Britain; 1800-1899; autobiographies (literary works); Autobiographies; Personal correspondence; Autobiographies.